Physico-chemical properties and extrusion behaviour of selected common bean varieties - Natabirwa, Hedwig; Muyonga, John H.; Nakimbugwe, Dorothy; Lung'aho, Mercy G. (Wiley, 2018)
Extrusion processing offers the possibility of processing common beans industrially into highly nutritious and functional products. However, there is limited information on properties of extrudates from different bean varieties and their association with raw material characteristics and extrusion conditions. In this study, physico‐chemical properties of raw and extruded Bishaz, K131, NABE19, Roba1 and RWR2245 common beans were determined. The relationships between bean characteristics and extrusion conditions on the extrudate properties were analysed.Extrudate physico‐chemical and pasting properties varied significantly (P < 0.05) among bean varieties. Expansion ratio and water solubility decreased, while bulk density, water absorption, peak and breakdown viscosities increased as feed moisture increased. Protein exhibited significant positive correlation (P < 0.05) with water solubility index, and negative correlations (P < 0.05) with water absorption, bulk density and pasting viscosities. Iron and dietary fibre showed positive correlation while total ash exhibited negative correlation with peak viscosity, final viscosity and setback. Similar trends were observed in principal component analysis.Extrudate physico‐chemical properties were found to be associated with beans protein, starch, iron, zinc and fibre contents. Therefore, bean chemical composition may serve as an indicator for beans extrusion behaviour and could be useful in selection of beans for extrusion. © 2017 Society of Chemical Industry